Your very private job agency: Job referrals based on residential location networks - Franziska Hawranek; Norbert Schanne (European Regional Science Association (ERSA), 2014)
Your very private job agency: Job referrals based on residential location networks This paper analyzes job referral effects that are based on residential location. We use georeferenced record data for the entire working population (liable to social security) and the corresponding establishments in the Rhine-Ruhr metropolitan area, which is Germany's largest (and EU's second largest) metropolitan area. We estimate the propensity of two persons to work at the same place when residing in the same neighborhood (reported with an accuracy of 500m500m grid cells), and compare the effect to people living in adjacent neighborhoods. We find a significant increase in the probability of working together when living in the same neighborhood, which is stable across various specifications. Additionally, we look at how referral effects differ for various groups like age, skill, ethnic groups and industry sectors. We find that especially low skilled workers make use of residential networks for job search, as well as some groups of immigrants. Especially migrants from the new EU countries as well as Italians and people from former Yugoslavia have a highly increased probability of working together when they share the same neighborhood. This is clear sign for network effects especially for some immigrant groups in the German labor market.JobFurther, we are able to investigate a number of issues in order to deepen the insight on actual job referrals: distinguishing between the effects on working in the same neighborhood and working in the same establishment ? probably the more accurate measure for job referrals ? shows that the latter yield overall smaller effects. Further, we find that clusters in employment although having a significant positive effect play only a minor role for the magnitude of the referral effect, which makes us confident that what we find is actually related to a true referral effect and not some spurious correlation. When we exclude short distance commuters, we find the same probabilities of working together, which reinforces our interpretation of this probability as a network effect. The paper investigates the effect of living together on the probability of working together. We find strong evidence for a positive and highly significant relationship, which is robust across several specifications and robustness tests, addressing common issues on the identification of neighborhood effects.
Keywords: J20; J46; R23; 330